A corpus-based list of academic English derivational suffixes - Suhandoko, S.; Ningrum, Dian Riesti (Universitas Pendidikan Indonesia, 2020)
The study reported in this paper aims to create a list of academic English derivational suffixes to help EFL teachers decide which derivational suffixes to be taught first and help their learners, especially those of higher education, expand their vocabulary size. Gardner and Davies’ (2014) 3,000-word list of Corpus of Contemporary American English (COCA) academic was analyzed following Hay (2002) and Plag’s (2006) frameworks by counting the number of words containing the suffixes. This study found 1,251 suffixed words in the corpus deriving from 41 suffixes, which comprise 22 noun suffixes, 13 adjectival suffixes, 4 verbal suffixes, and 2 adverbial suffixes. The suffixes were then ordered into 3 levels based on the frequency; 22 suffixes are put in Level 1, 12 suffixes in Level 2, and 7 suffixes in Level 3. Considering the high frequency, all suffixes in Level 1 should gain more attention of the teachers. The more frequent occurrence of the suffix in a variety of context will provide a greater chance for the learners to get more exposure. Hence, mastering it will likely expand learners’ vocabulary size through combining the suffix and existing base.